Efficacy of iron fortification and protein efficiency in fortified blended foods and extruded rice in rats - Ward, Erin Jean (Kansas State University, 2019)
Background & Objectives: Both fortified blended foods (FBFs) and fortified rice are important food aid products for addressing protein undernutrition and iron deficiencies globally and were evaluated in two rat studies. We previously found that extruded sorghum-soy blend (SSB) FBFs were equally nutritious compared to corn-soy blend (CSB) FBFs. In the first study, we assessed SSB and CSB FBFs with protein primarily provided by soy flour and compared outcomes to previously developed blends with whey protein concentrate (WPC) to evaluate reduced-cost options (FBF study). In the second study, we compared iron outcomes from four different iron fortificants in extruded rice (rice study). Ferric phosphate (FePO₄) and ferric pyrophosphate (FePP) were selected for their suitable organoleptic properties. Micronized FePP (µFePP) and the addition of trisodium citrate (TSC) and citric acid (CA) to FePP (FePP+TSC+CA) were suggested to increase FePP absorption. Methods: In the FBF study, SSB and CSB FBFs were developed with soy flour and 0–15% sucrose in SSBs and 0–10% sucrose in CSBs. SSB and CSB FBFs with 9.5% WPC and 15% sucrose served as comparison diets. In the rice study, extruded rice kernels were fortified with one of four iron fortificants: FePO₄, FePP, µFePP, or FePP+TSC+CA (ratio: 1:2.1:0.1). Each extruded rice was blended at 1% with natural white rice, soy protein isolate, and soybean oil and cooked. In each study, weanling, male Sprague Dawley rats were individually housed and randomly assigned to a test or control diet (n=9-10). Food intake was measured every other day (FBF) or daily (rice) and body weights were taken weekly. At study conclusion (FBF: 28 days; rice: 21 days), blood and livers were collected to evaluate iron outcomes and body scans were performed to assess body composition and bone mineral density (BMD). Results: In the FBF study, there were no differences in food intake, weight gain, lean mass, and iron outcomes among FBF groups. The CSB groups without WPC had significantly lower caloric efficiency and all groups without WPC had significantly lower protein efficiency compared to the groups with WPC. In combined analyses, groups consuming FBFs with 15% sucrose had significantly lower BMD compared to FBF groups with ≤10% sucrose. In the rice study, all rice groups had significantly lower moisture-adjusted total food intake, weight gain, and BMD compared to the control group with no differences in these outcomes between the rice groups. Hemoglobin concentrations were significantly higher in FePP and µFePP groups compared to FePO₄ and control groups. Hepatic iron concentrations were significantly higher in FePP, µFePP, and FePP+TSC+CA groups compared to FePO₄ and control groups. Conclusions: All factors considered, extruded SSB FBFs with soy protein and ≤10% sucrose are an efficacious alternative to WPC-containing FBFs in rats. While the rice study outcomes need to be interpreted with caution because of poor growth, these results suggest FePP leads to better iron outcomes than FePO₄. However, neither micronizing nor adding CA+TSC to FePP improved iron outcomes.
Keywords: Iron bioavailability; Protein quality; Food aid; Fortified blended foods; Fortified rice